(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
When talking about marriage, the Legal Regulation of Marriage Capitulations must be weighed, that is, during the marriage process, couples must know the benefit of counting as a requirement the matrimonial capitulations, it is an economic regime, of legal certainty, when the marriage union must be liquidated, of the negative thought that one has of what the marriage and its administration represents. The capitulations is a legal act allied to the marriage, which can undoubtedly strengthen the support for both parties, unfortunately these types of procedures are not carried out, and when the marriage is dissolved with the divorce, the conflict begins, where the consorts, do not want to share or liquidate the conjugal patrimony.